2019
DOI: 10.1371/journal.pone.0215406
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of gonads and external sexual characters of the protandric simultaneous hermaphrodite peppermint shrimp, Lysmata vittata (Caridea: Hippolytidae)

Abstract: The peppermint shrimp Lysmata vittata (Caridea: Hippolytidae) is a marine caridean shrimp popular in marine aquarium trade. The species is known to display the sexual system of protandric simultaneous hermaphrodite. In this study, based on captive bred specimens, the complete ontogenetic gonad development of L . vittata was studied both morphologically and histologically, from newly settled juveniles until they reached euhermaphrodite phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In M. rosenbergii, TAP was distributed on terminal ampullae and sperms, as it participates in sperm proteolytic activity and plays a key role in sperm maturation (56). We hypothesized that TAP play similar functional roles in L. vittata sperm, in gonad of both MP and EP (15). Moreover, TPM values of neuroparsins and RPCH are higher than 15 in MP.…”
Section: Peptides/gpcrs Expressionmentioning
confidence: 96%
See 4 more Smart Citations
“…In M. rosenbergii, TAP was distributed on terminal ampullae and sperms, as it participates in sperm proteolytic activity and plays a key role in sperm maturation (56). We hypothesized that TAP play similar functional roles in L. vittata sperm, in gonad of both MP and EP (15). Moreover, TPM values of neuroparsins and RPCH are higher than 15 in MP.…”
Section: Peptides/gpcrs Expressionmentioning
confidence: 96%
“…In this study, expression levels of two IAGs in MP shrimp were higher than in EP shrimp, of which, the TPM value of IAG1 was 76 in MP shrimp, but not expressed in EP shrimp. In L. vittata, it was reported that the male external sexual character had disappeared whereas testicular part had some degree of degeneration in EP shrimp (15), of which were ascribed to the down-regulation of IAGs. In M. rosenbergii, silencing of IAG not only arrested the degeneration of male secondary sexual characteristics and testis, but also prevented testicular spermatogenesis (2).…”
Section: Key Peptidesmentioning
confidence: 99%
See 3 more Smart Citations